IMPLEMENTATION OF LOGIC MODEL TO IMPROVE EDUCATION QUALITY: A CASE STUDY AND IMPLEMENTATION ANALYSIS - Muhammad Daniel; Dian Mohammad Hakim; Ika Ratih Sulistiani (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
Education is a fundamental pillar to produce a competent and highly competitive generation, which faces several challenges to realize it. The main challenges include limited resources and a lack of innovative teaching methods. This study examines the implementation of the Logic Model at MIN 13 Pidie Jaya to improve educational quality in a remote area. The research also investigates the implementation process through the lens of Constructivist Learning Theory and parental involvement, and evaluates specific outcomes that indicate quality improvement. This study employed a qualitative case study approach. Data were collected through interviews with eight informants, observations, and document analysis. The findings indicate that the Logic Model supports structured and measurable program planning. Notable impacts include the improvement of teacher participation in training, technology-equipped classrooms, student involvement in extracurricular activities, academic performance, and stronger parental engagement. The study recommends continuous teacher development, regular evaluation, and strengthened school–community collaboration.